Types of Plots in Khaled Hosseini's The Kite Runner - Chaira, Uswatul; Yuniarti, Yuniarti (Accentia: Journal of English Language and Education, 2020)
This study discusses the types of plot used by Khaled Hosseini in his novel The Kite Runner. Plot is an element in a novel which is necessary in order to understand the storyline of the novel. The study was a descriptive study. The results showed that the plots found in The Kite Runner included maturation, escape, rescue, love, revenge, the riddle, quest, underdog, sacrifice, ascension and rivalry.